Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T20:24:43+01:00
A)8x+6y-4z = 2(4x+3y-2z)
b)6a+10ab+8ac = 2a(3+5b+4c)
c)8x+12x²-16x³ = 4x(2+3x-4x²)
d)3abc+6acd-9abd = 3a(bc+2cd-3bd)
e)5x⁴-25x³-10x² = 5x²(x²-5x-2)
1 4 1
2010-02-06T20:25:39+01:00
A)8x+6y-4z = 2(4x+3y-2z)
b)6a+10ab+8ac= 2a(3+5b+4c)
c)8x+12x²-16x³= 4x(2+3x-4x²)
d)3abc+6acd-9abd= 3a(bc+2cd-3bd)
e)5xdo potegi czwartej-25x³-10x²= 5x²(x²-5x-2)
2010-02-06T20:28:41+01:00
A)8x+6y-4z= 2(4x+3y-2z)
b)6a+10ab+8ac = 2a(3+5b+4c)
c)8x+12x(kwadrat)-16x(szescian) = 4x(2+3x-4x(kwadrat))
d) 3abc+6acd-9abd = 3a(bc+2cd-3bd)
e) 5x (do 4)-25x(szescian)-10x(kwadrat)= 5xkwadrat(xkwadrat-5x-2)
;)